2004
DOI: 10.1007/bf03167075
|View full text |Cite
|
Sign up to set email alerts
|

p53: Twenty five years understanding the mechanism of genome protection

Abstract: This year the p53 protein, also known as "guardian of the genome", turns twenty five years old. During this period the p53 knowledge have changed from an initial pro-oncogene activity to the tumorsupressor p53 function. p53 is activated upon stress signals, such as gamma irradiation, UV, hypoxia, virus infection, and DNA damage, leading to protection of cells by inducing target genes. The molecules activated by p53 induce cell cycle arrest, DNA repair to conserve the genome and apoptosis. The regulation of p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 160 publications
(132 reference statements)
4
82
0
2
Order By: Relevance
“…[14][15][16][53][54][55][56][57] It was, therefore, of interest to look for a possible variation in the functional status of p53 in the T-cell lines employed in this study that might explain the different patterns of Tax effects on NER in these cells. Although several laboratories claim that Jurkat cells are p53 null, we have previously shown that the Jurkat cells used in our experiments, express comparable levels of both w.t.…”
Section: Tax Effect On Ner In Human T-cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][53][54][55][56][57] It was, therefore, of interest to look for a possible variation in the functional status of p53 in the T-cell lines employed in this study that might explain the different patterns of Tax effects on NER in these cells. Although several laboratories claim that Jurkat cells are p53 null, we have previously shown that the Jurkat cells used in our experiments, express comparable levels of both w.t.…”
Section: Tax Effect On Ner In Human T-cellsmentioning
confidence: 99%
“…9,12,13 There are indications that p53 is directly involved in DNA repair by either physical interaction with, or modulation of the synthesis of DNA repair-associated factors. 14,15 In addition, p53 recruits histone acetylases and deacetylases for chromatin remodeling at the damage sites, which is essential for efficient detection of the lesions. 16 Human T-cell leukemia virus type-1 (HTLV-1) is etiologically implicated with adult T-cell leukemia (ATL), tropical spastic paraparesis/HTLV-1 associated myelopathy (TSP/HAM) and certain other clinical disorders, 17,18 none of which efficiently responds to presently known therapeutic approaches.…”
mentioning
confidence: 99%
“…3A and 5B). Certainly, phosphorylation of p53 can occur in response to a variety of cellular stresses besides strand breaks, such as that caused by UV irradiation or hypoxia (43). However, phosphorylation of Chk2, like gH2AX, is considered to be more specific to the cellular response to DNA DSBs (23,44).…”
Section: Discussionmentioning
confidence: 99%
“…Germ-line mutations in TP53 are known to cause a number of recognized human cancers including Li-Fraumeni syndrome (9). When TP53 itself is not genetically inactivated, other mechanisms, such as loss of heterozygosity by deletion of the 17p locus or gene methylation, may contribute to reduced p53 activity (10)(11)(12)(13)(14)(15). The polymorphic nature of the TP53 gene and its central role in cell cycle regulation have highlighted it as a good potential candidate susceptibility gene for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%